The Regulation of the AdcR Regulon in Streptococcus pneumoniae Depends Both on Zn2+- and Ni2+-Availability - Manzoor, Irfan; Shafeeq, Sulman; Afzal, Muhammad; Kuipers, Oscar P. (Frontiers in Cellular and Infection Microbiology, 2015)
By using a transcriptomic approach, we have elucidated the effect of Ni2+ on the global gene expression of S. pneumoniae D39 by identifying several differentially expressed genes/operons in the presence of a high extracellular concentration of Ni2+. The genes belonging to the AdcR regulon (adcRCBA, adcAII-phtD, phtA, phtB, and phtE) and the PsaR regulon (pcpA, prtA, and psaBCA) were highly upregulated in the presence of Ni2+. We have further studied the role of Ni2+ in the regulation of the AdcR regulon by using ICP-MS analysis, electrophoretic mobility shift assays and transcriptional lacZ-reporter studies, and demonstrate that Ni2+ is directly involved in the derepression of the AdcR regulon via the Zn2+-dependent repressor AdcR, and has an opposite effect on the expression of the AdcR regulon compared to Zn2+.